La magia de la cocina - Kastelic Vukadinović, Uršula (Verba hispanica, 2013)
In the paper we analyze some of the stylistic characteristics of the novel Like Water for Chocolate from the perspective of a non-Mexican reader. The narrator of the story interlaces the typical linguistic structures specific to cooking recipes and the story of a forbidden love between Tita and Pedro. As a good cook she gives advice, describes the procedures for the preparation of the food, all of which she intertwines with the story as once told to her, which is explicitly expressed by using reporting verbs. We found out that one of the characteristics of the novel is the visualization of the story. The author herself says that her literary creation is based on visual images and that afterwards she turns them into a story. In the novel this is reflected in Tita`s intense response to sensory stimuli. In the article, we highlight examples from the text, structured according to the predominant senses involved. Through the food that Tita is preparing Tita and Pedro establish an unusual, passionate and sensual relationship. Among the ingredients for the dishes that are connected to their love story, the reader encounters many unknown Mexican cultural expressions, which do not hinder the understanding of the story. The text shows that we are dealing with a dish or an ingredient that is mentioned at the beginning as a part of the recipe or presented in such a context. Therefore, the coherence of the text is maintained. The reader takes pleasure in the reading that transports him to the distant worlds of magical realism.
Keywords: latinskoameriške književnosti; Esquivel, Laura: Kot voda za čokolado; študije; jezik; Language